65=x+5(x+1)

Simple and best practice solution for 65=x+5(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 65=x+5(x+1) equation:



65=x+5(x+1)
We move all terms to the left:
65-(x+5(x+1))=0
We calculate terms in parentheses: -(x+5(x+1)), so:
x+5(x+1)
We multiply parentheses
x+5x+5
We add all the numbers together, and all the variables
6x+5
Back to the equation:
-(6x+5)
We get rid of parentheses
-6x-5+65=0
We add all the numbers together, and all the variables
-6x+60=0
We move all terms containing x to the left, all other terms to the right
-6x=-60
x=-60/-6
x=+10

See similar equations:

| 4(x-1/2)=6 | | 3x-175=x+125 | | y+15=-45. | | 4.a=120 | | 17r-16r=19 | | 13x+27=10x+18 | | 18m-16m=12 | | 35=x+3(x+2) | | (3x+15)(x-5)=0 | | (x+30)+(x-10)+(x+40)=180 | | 0.4p=4500 | | 3(2x-5)=9+3(x-3) | | 60+5d=70+4d | | 8=t/3+5 | | 4(x+26)=130 | | 5(2x+7=54 | | 5=x(5+9)12 | | 5=½x(5+9)12 | | n/9=-2/7 | | 5.5x-5.5=5.5 | | 5=(5+9)x12 | | (3-x)(4x-2)=-4x^2-(10x-(15x+12)) | | 1000=25x+250 | | 5x+9/3x+4=2 | | -33=3x+66 | | (3-x)(4x-2)=-4x²-(10x-(15x+12)) | | 1/2k-7=1/3k-4 | | 0,5x+2=4,5 | | 2(5-4x)=-3x-32 | | 15x-28=92 | | 8p+16=2+7p | | x^2-3.625x=-2.5 |

Equations solver categories